Etnografi Navigasi Bugis Karya Gene Ammarell - Anwar Anwar (Emik, 2018)
Nowdays, phenomenology as one of epistemologies in social science has contributed to the Anthropology. The phenomenological roots as a philosophy also enter and connected to the social science, especially in Anthropology. This journey was being started from Edmund Husserl to Alfred Schutz. Ethnoscience as part of the paradigms from phenomenology is a new identity in many Anthropological research. There are so many ethnographical researches which has using this perspective, but not many people who wants to focus and specific to explain the epistemology from that research. This article intends to fill that empty, in order to ethnographical research is not only we read and analyze as a practical reasons, but philosophical idea. This contribution has a big impact for Anthropology’s design in the future. Methodological research from this article based on literature study not fieldwork as a usual (like observation and interview). Etnografi Navigasi Bugis by Gene Ammarell becomes an example to study about the epistemology from ethnographical research. This ethnography is proven to be a phenomenological research and containing some assumptions that Bugis’ fisherman in Balabaloang has local knowledge about ocean navigation. What Gene Ammarell doing can attain a knowledge and consciousness (collective) about fisherman’s navigation in Balabaloang. Therefore, he also called as phenomenologist.